Sustainable Slow-Pyrolysis Simulation of 12 Lignocellulosic Bio-wastes: CO2 Emission, Energy, and Water Consumption. Issue 1 (1st January 2022) - Zalazar-Garcia, D; Fernandez, A; Rodriguez-Ortiz, L; Rodriguez, R; Mazza, G
Abstract: The development and increase of the agro-industrial activity generate bio-waste that represents significant quantities and causes environmental impacts, as residual effluents and solid wastes. These bio-wastes can be converted into different products through the pyrolysis processes (biochar, bio-oil, and gas). In this work, the pyrolysis at 673, 773, and 873 K of 12 types of bio-waste characterized by their elemental composition was assessed through the simulation process. Cape Open to Cape Open Simulator (COCO) free software was used in simulations. Thus, the biochar, bio-oil, and gas yields were predicted. Also, the energy, water consumption, and CO2 emission were calculated for each type of bio-waste. The marc and the stalk of white grape presented the highest biochar and bio-oil yields (30.7 and 53.1 %wt) at 673 K. The pistachio green shell presented the highest gas yield, 53.7 %wt at 873 K. The maximum energy consumption and CO2 emissions founded were 13.72 kWh and 3.72 kg/h for the stalk of white grape at 873 K respectively, while the lowest energy consumption and CO2 emission were 9.22 kWh and 2.31 kg/h for plum pits at 773 K respectively. The highest water consumption was 25.86 kg/h for the stalk of red grape at 773 K, while the lowest value was 14.30 kg/h for plum pits at 773 K.